The Incorporation of 4C Skills in Senior High School English Teachers’ Lesson Plans - Muhammad Fadil Radifan; Ratna Dewanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2020)
This study aims at describing how the 4C skills are incorporated in senior high school English teachers’ lesson plans and investigating the lesson plan components in which those skills are incorporated. The data for this qualitative study were collected through content analyses on ten lesson plans by three senior high school teachers in Jakarta. The study found that all lesson plans that were analyzed have incorporated all of the four 4C skills, which consist of creativity and innovation, critical thinking and problem solving, communication, and collaboration. Among all indicators of the 4C skills’ incorporation, some were found to be incorporated in all lesson plans regardless of their topics, while others were more dominantly incorporated in lesson plans that discuss certain topic categories. The findings of the study also showed that most 4C skills were incorporated in the same four categories of lesson plan components: learning steps, assessment, learning methods, and indicators of competence achievement. An exception to this is the collaboration skill, which was not incorporated in components involving indicators of competence achievement. These findings are expected to aid teachers in specifying 4C skill aspects to incorporate in their lesson plans and the components to incorporate those aspects into.